Photocurrent enhancements of organic solar cells by altering dewetting of plasmonic Ag nanoparticles - Fleetham, Tyler; Choi, Jea-Young; Choi, Hyung Woo; Alford, Terry; Jeong, Doo Seok; Lee, Taek Sung; Lee, Wook Seong; Lee, Kyeong-Seok; Li, Jian; Kim, Inho (NATURE PUBLISHING GROUP, 2015)
Incorporation of metal nanoparticles into active layers of organic solar cells is one of the promising light trapping approaches. The size of metal nanoparticles is one of key factors to strong light trapping, and the size of thermally evaporated metal nanoparticles can be tuned by either post heat treatment or surface modification of substrates. We deposited Ag nanoparticles on ITO by varying nominal thicknesses, and post annealing was carried out to increase their size in radius. PEDOT: PSS was employed onto the ITO substrates as a buffer layer to alter the dewetting behavior of Ag nanoparticles. The size of Ag nanoparticles on PEDOT: PSS were dramatically increased by more than three times compared to those on the ITO substrates. Organic solar cells were fabricated on the ITO and PEDOT: PSS coated ITO substrates with incorporation of those Ag nanoparticles, and their performances were compared. The photocurrents of the cells with the active layers on PEDOT: PSS with an optimal choice of the Ag nanoparticles were greatly enhanced whereas the Ag nanoparticles on the ITO substrates did not lead to the photocurrent enhancements. The origin of the photocurrent enhancements with introducing the Ag nanoparticles on PEDOT: PSS are discussed.
Keywords: EFFICIENCY; POLY(3-HEXYLTHIOPHENE); DEPENDENCE; THICKNESS; PARTICLE; LAYER; FILM